A Small Molecule p75NTR Ligand Protects Neurogenesis After Traumatic Brain Injury. (November 2013) - Shi, Jian; Longo, Frank M.; Massa, Stephen M.
Abstract The p75 neurotrophin receptor (p75NTR) influences the proliferation, survival, and differentiation of neuronal precursors and its expression is induced in injured brain, where it regulates cell survival. Here, we test the hypotheses that pharmacologic modulation of p75NTR signaling will promote neural progenitor survival and proliferation, and improve outcomes of traumatic brain injury (TBI). LM11A‐31, an orally available, blood‐brain barrier‐permeant small‐molecule p75NTR signaling modulator, significantly increased proliferation and survival, and decreased JNK phosphorylation, in hippocampal neural stem/progenitor cells in culture expressing wild‐type p75NTR, but had no effect on cells expressing a mutant neurotrophin‐unresponsive form of the receptor. The compound also enhanced the production of mature neurons from adult hippocampal neural progenitors in vitro. In vivo, intranasal administration of LM11A‐31 decreased postinjury hippocampal and cortical neuronal death, neural progenitor cell death, gliogenesis, and microglial activation, and enhanced long‐term hippocampal neurogenesis and reversed spatial memory impairments. LM11A‐31 diminished the postinjury increase of SOX2‐expressing early progenitor cells, but protected and increased the proliferation of endogenous polysialylated‐neural cell adhesion molecule positive intermediate progenitors, and restored the long‐term production of mature granule neurons. These findings suggest that modulation of p75NTR actions using small molecules such as LM11A‐31 may constitute a potent therapeutic strategy for TBI. Stem Cells2013;31:2561–2574